The genus Tychius Germar (Coleoptera: Curculionidae: Curculioninae) in China, with description of three new species - Jiang, Chunyan; Caldara, Roberto; Zhang, Runzhi (Zootaxa, 2020)
The species of the weevil genus Tychius Germar, 1817 (Curculionidae: Curculioninae: Tychiini) in China are herein reviewed. Thirty-five taxa are reported, 14 already known from China: T. albolineatus Motschulsky, 1860, T. herculeanus Reitter, 1902, T. uralensis Pic, 1902, T. longulus Desbrochers des Loges, 1873, T. praescutellaris (Pic, 1902), T. tectus LeConte, 1876, T. oriens A. Hoffmann, 1964, T. thompsoni Caldara, 1990, T. perrinae Caldara, 1990, T. ovalis Roelofs, 1875, T. medicaginis C. N. F. Brisout de Barneville, 1863, T. meliloti Stephens, 1831, T. kerulensis (Bajtenov, 1981), T. breviusculus Desbrochers des Loges, 1873; 18 cited for the first time from China: T. rufirostris Schoenherr, 1832, T. hauseri Faust, 1889, T. squamulatus Gyllenhal, 1835, T. flavus Becker, 1864, T. aureolus Kiesenwetter, 1852, T. junceus (Reich, 1797), T. crassirostris Kirsch, 1871, T. vossi Caldara, 1990, T. picirostris (Fabricius, 1787), T. morawitzi Becker, 1864, T. winkleri (Franz, 1940), T. urbanus Faust, 1885, T. sulphureus Faust, 1881, T. bajtenovi Caldara, 1986, T. kaszabi (Bajtenov, 1977), T. gracilitubus (Bajtenov, 1977), T. hedysaricus Karasyov, 1991, T. crassifemoris (Bajtenov, 1977); and three new to science: T. tachengicus Jiang & Caldara n. sp., T. obrieni Jiang & Caldara n. sp., T. zhangi Jiang & Caldara n. sp. A key to the species is provided. Diagnosis, comparative notes and distribution are reported for each species. Dorsal and lateral habitus, as well as details of rostrum, femur, tibia, genitalia, tarsus and claw are illustrated.